2020
DOI: 10.12982/cmujns.2021.016
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Model for the Total Daily COVID-19 Cases with Herd Immunity Policy

Abstract: The spread of coronavirus disease 2019 (COVID-19) has caused a pandemic, and policies for fighting COVID-19 have been enacted by the governments of most countries. The herd immunity policy is the policy that Sweden is using to fight COVID-19. The purpose of this research is to estimate the number of total COVID-19 cases in Sweden in which herd immunity is being encouraged. A logistic model was selected as the predictive model for estimating the number of COVID-19 cases in Sweden and the other Nordic countries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The parameters for the exponential growth curve were estimated by the least square method by using the number of total COVID-19 cases in Thailand from February 15 th , 2020 to March 25 th , 2020 which is the period before the emergency decree announcement. The results showed that the parameters 0 16.07, 0.08 C r = =…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The parameters for the exponential growth curve were estimated by the least square method by using the number of total COVID-19 cases in Thailand from February 15 th , 2020 to March 25 th , 2020 which is the period before the emergency decree announcement. The results showed that the parameters 0 16.07, 0.08 C r = =…”
Section: Resultsmentioning
confidence: 99%
“…Comparisons and examples between the flattened curve policy and the herd immunity policy are discussed. Sweden is the country in which the herd immunity policy has firstly been used to protect and control the COVID-10 outbreak since the worldwide pandemic time of coronavirus disease 2019 [16]. The other Nordic countries-Norway, Finland, and Denmark-including Thailand have applied the flattened curve policy to fight the COVID-19 outbreak.…”
Section: Figure 1 Estimated Exponential Growth Curve Before and After The Emergency Decree (Ed)mentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal parameters or estimated parameters K, r, C can be solved by the least square error method. The validation and accuracy of the predictive growth curve time series are based on statistic the coefficient of determination (R 2 ) and the root mean squared percentage error (RMSPE) [13][14].…”
Section: Predictive Time Series and Its Parameter Estimation For The Covid-19 Outbreakmentioning
confidence: 99%
“…As the above literature reviews, the models for describing the COVID-19 outbreak are based on time independent variable. For example, the forecasting models are the models with time independent variables such as the logistic and Gompertz models [1][2][3], the Bertalanffy model [4], the Boltzmann growth curve [5,6], and Regression analysis [7,8]. The mathematical models, a system of differential equations, are the models with time independent variable such SEIQCRW model [19], SIR model [20], SEIR model [21], and SEIQRD [24].…”
mentioning
confidence: 99%